Respuesta :

-2x^2 + 10x + 9 =0
multiply whole equation by -1
2x^2  -10x -9 =0

(sqrt2x)^2  -2(sqrt2x)(5/
sqrt2) -9=0
add (5/sqrt2)^2 on both sides
(sqrt2x)^2  -2(sqrt2x)(5/sqrt2) + (5/sqrt2)^2-9=(5/sqrt2)^2

a^2-2ab+b^2=(a-b)^2
(sqrt2x  -  5/sqrt2)^2=(5/sqrt2)^2+9

(sqrt2x  -  5/sqrt2)^2=21.5

taking squareroot on both sides

sqrt2x  -  5/sqrt2 = +-4.64
so
sqrt2x  -  5/sqrt2 = +4.64       or         sqrt2x  -  5/sqrt2 = -4.64
sqrt2x = 4.64 +  5/sqrt2                     sqrt2x = -4.64 +  5/sqrt2
sqrt2x =8.18                                         sqrt2x = -1.1045
x=8.18/sqrt2                                        x= -1.1045/sqrt2
x=5.78                                                 x=-0.781
The picture above is the answer if you have any question, feel free to ask and if not it would be nice if you give me a brainliest answer :)
Ver imagen stevemosby0
ACCESS MORE